Pengaruh Penambahan Ikan Tuna Asap Terhadap Karakteristik Kimia Kukis Kenari Sebagai PMT Balita Stunting - Mailoa, Meitycorfrida; Tuhumury, Helen C D; Burnama, Matelda (Universitas Pattimura, 2024)
Cookies, a type of snack favored by children and adults, are typically rich in energy but low in protein. Cookies made with canarium nuts as a raw material offer an alternative to increase protein value while providing energy. The issue of stunting, which has become a national concern, requires attention from various sectors, including universities contributing through innovative research. One such research topic is the addition of smoked tuna meat to canarium nut cookie dough, aiming to enhance the nutritional value of canarium nut cookies and provide a supplementary food option for children under five affected by stunting. This study aimed to analyze the effect of adding smoked tuna meat on the chemical characteristics of canarium nut cookies, which can serve as supplementary food to address stunting issues. The study employed a Completely Randomized Design with one factor: the concentration of smoked tuna meat, comprising six levels: 0%, 2%, 4%, 6%, 8%, and 10% smoked tuna meat. Each treatment level was repeated twice. The results indicated that canarium nut cookies with a 2% concentration of smoked tuna meat were the best according to the Indonesia National Standard (SNI), exhibiting the following chemical content: moisture content of 4.99%, ash content of 1.36%, protein content of 12.7%, fat content of 12.7%, and carbohydrate content of 70.26%.